2021
DOI: 10.3389/fcell.2021.692269
|View full text |Cite
|
Sign up to set email alerts
|

Ser71 Phosphorylation Inhibits Actin-Binding of Profilin-1 and Its Apoptosis-Sensitizing Activity

Abstract: The essential actin-binding factor profilin-1 (Pfn1) is a non-classical tumor suppressor with the abilities toboth inhibit cellular proliferation and augment chemotherapy-induced apoptosis. Besides actin, Pfn1 interacts with proteins harboring the poly-L-proline (PLP) motifs. Our recent work demonstrated that both nuclear localization and PLP-binding are required for tumor growth inhibition by Pfn1, and this is at least partially due to Pfn1 association with the PLP-containing ENL protein in the Super Elongati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 51 publications
(138 reference statements)
0
6
0
Order By: Relevance
“…All cell lines including PANC-1, MIA PaCa-2, Capan-1, Pa01C, and HEK293T were mycoplasma-tested annually and cultured in high glucose DMEM supplemented with 10% fetal bovine serum and 50 mg/mL gentamicin. Lentiviruses were produced by transient transfection of HEK293T cells as previously described [25,[29][30][31].…”
Section: Cell Linesmentioning
confidence: 99%
See 2 more Smart Citations
“…All cell lines including PANC-1, MIA PaCa-2, Capan-1, Pa01C, and HEK293T were mycoplasma-tested annually and cultured in high glucose DMEM supplemented with 10% fetal bovine serum and 50 mg/mL gentamicin. Lentiviruses were produced by transient transfection of HEK293T cells as previously described [25,[29][30][31].…”
Section: Cell Linesmentioning
confidence: 99%
“…Briefly, cells were grown in 96-well plates, treated, and detergent extracted for 8 min, fixed by 4% paraformaldehyde for 15 min, washed by PBS/0.1% Triton X-100, blocked with 5% normal goat serum for 60 min, and incubated with primary antibodies (1:1000; custom-made mouse anti-pSer 784 -VCP and rabbit anti-γH2AX, Cell Signaling #9718) overnight at 4 • C. Cells were washed with PBS/0.1% Triton X-100, incubated with Alexa 488 or 594-conjugated secondary antibodies (Invitrogen, Waltham, MA, USA) for 2 h at room temperature, washed with PBS/0.1% Triton X-100, and counterstained with DAPI. Fluorescence images were acquired on an inverted Olympus IX70 microscope equipped with CellSens software as previously described [25,30,31].…”
Section: Immunofluorescence Staining and Image Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phosphorylation of Ser 71 inhibits actin-binding of profilin-1. 30 The mechanisms by which toxic nanoparticles induce pulmonary disease remain to be elucidated. In this study, we examined whether nanoparticles play a role in lung disease employing two-dimensional polyacrylamide gel electrophoresis (2D-PAGE) and matrix-assisted laser desorption/ionization time-of-flight/time-of-flight mass spectrometry (MALDI-TOF/TOF MS) of endothelial cells, and examined protein expression in the lungs of a mouse model of asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Post-translational modifications (PTM), such as nitration and phosphorylation (S137, Y219), of profilin 1 alter its biological functions [16][17][18]. Profilin is also regulated by phosphorylation at sites T89, S71, Y129 [19][20][21]. It has been demonstrated that phosphorylation of profilin is counter acted by protein phosphatase-1, and the switch between the two states regulates cell proliferation and survival [22].…”
Section: Introductionmentioning
confidence: 99%